EFFECTIVENESS OF MINDFULNESS BASED THERAPY PROGRAM ON THE LEVEL OF DRINKING PROBLEMS AND THE RELAPSE PERIOD OF ALCOHOL DEPENDENCE AT PSYCHIATRIC WARD, NONGBUALAMPHU HOSPITAL - Chaipratanpong, Karnthibhorn; Panuwet, Rueangsiri (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to: 1) level of drinking problem of alcohol dependence patients among the experimental group by a Mindfulness Based Therapy Counseling Program (MBTC) and the control group by a Regular Activity Therapy. 2) relapse period of alcohol dependence patients among the experimental group by a MBTC program and the control group by a Regular Activity Therapy, after discharge from the hospital. It was a quasi-experimental research methodology with 2 groups, pre- experiment and post-experiment. A sample of 116 people obtained from the power analysis of sample size, the ratio was 1 to 3, divided into the experimental group treated a MBTC program of 28 people and the control group treated by Regular Activity Therapy of 88 people, totaling 116 people. Which were eligible patients with the assessment scores less than 4 for symptoms of alcohol deprivation, none of psychiatric symptoms or remission that can be able to learn by following up in after treatment in 3 stages were 2 weeks, 4 weeks and 12 weeks. The data were analyzed using baseline statistics, frequency, percentage, mean, standard deviation. Interpretation of results was compared between groups using T-test. The duration of alcohol relapse was analyzed in both groups by Multivariable Flexible Parametric survival regression. The research results were: 1) level of drinking problems pre - experimental period and post-experiment period found that the experimental group had a level of drinking problems. It was statistically significantly different from the control group (p<0.001). 2) The relapse period found that in the 12 weeks, the experimental group was able to reduce the relapse by 99.4%, especially in the first 2 weeks and average 72 days longer than control group to repeat to be an alcohol dependence. The 95 percentage of confidence interval was between 68 and 78 days with statistical significance. (p<0.001).